2017
DOI: 10.1160/th17-01-0068
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of apixaban versus warfarin in non-valvular atrial fibrillation patients in “real-world” clinical practice

Abstract: Summary The ARISTOTLE trial showed a risk reduction of stroke/systemic embolism (SE) and major bleeding in non-valvular atrial fibrillation (NVAF) patients treated with apixaban compared to warfarin. This retrospective study used four large US claims databases (MarketScan, PharMetrics, Optum, and Humana) of NVAF patients newly initiating apixaban or warfarin from January 1, 2013 to September 30, 2015. After 1:1 warfarin-apixaban propensity score matching (PSM) within each database, the resulting patient record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
141
5
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 148 publications
(164 citation statements)
references
References 27 publications
10
141
5
8
Order By: Relevance
“…The third study compared the effectiveness of apixaban versus warfarin in nonvalvular atrial fibrillation (NVAF) patients . In the original study, data were pooled from MarketScan and 3 other large US claims databases (PharMetrics, Optum, and Humana) and patients were followed up for stroke/systemic embolism (SE) and major bleeding.…”
Section: Simulation Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The third study compared the effectiveness of apixaban versus warfarin in nonvalvular atrial fibrillation (NVAF) patients . In the original study, data were pooled from MarketScan and 3 other large US claims databases (PharMetrics, Optum, and Humana) and patients were followed up for stroke/systemic embolism (SE) and major bleeding.…”
Section: Simulation Experimentsmentioning
confidence: 99%
“…The third study compared the effectiveness of apixaban versus warfarin in nonvalvular atrial fibrillation (NVAF) patients. 32 In the original study, data were pooled from MarketScan and 3 other large US claims databases (PharMetrics, Optum, and Humana) and patients were followed up for stroke/systemic embolism (SE) and major bleeding. Using MarketScan data only, we identified 163 336 NVAF patients that were newly initiated on apixaban (approved by the US Food and Drug Administration in December 2012) or warfarin from January 1, 2013, to December 31, 2015, (8% initiated on apixaban versus 92% on warfarin).…”
Section: Empirical Datamentioning
confidence: 99%
“…Since 2014, several real‐world observational studies investigated the bleeding risk of NOAC in many countries . Annex 10 reports some characteristics of these postapproval published studies and shows heterogeneity for many aspects: most of them used retrospective data from nationwide administrative or insurance databases with limited clinical information – no access for patient's mortality .…”
Section: Discussionmentioning
confidence: 99%
“…International multicentre trials have shown noninferiority to warfarin in patients with AF with lower risk of intracranial haemorrhage but a higher risk of gastrointestinal bleeding . Several reports from registries and analysis of claims databases have recently suggested, compared with VKA, a similar safety profile of NOAC in the community and in randomized trials. However, meta‐analyses highlighted inconsistency among those observational studies using different designs: Weeda et al.…”
Section: Introductionmentioning
confidence: 99%
“…For example, assuming two sets of event rates for major bleeding of 2.5/100 PYs (OAC A 1 ) vs 2.0/100 PYs (OAC B 1 ) or 6.0/100 PYs (OAC A 2 ) vs 4.8/100 PYs (OAC B 2 ), the resulting hazard ratios would be identical (at 1.25), but absolute differences and interpretation of the clinical relevance would vary substantially (Δ 1 = 0.5%/100 PYs, NNH = 200; and Δ 2 = 1.2%/100 PYs, NNH = 84). Most claims analyses of OAC in NVAF patients report both hazard ratios and absolute risk rates, with bleeding event estimates of the latter ranging from 2.5 to 7.5 events/100 PYs. Given the potential impact that overestimation (or underestimation) of bleeding risk may have on the interpretation of claims database study results, it is important that steps are taken whenever possible to assure the most accurate estimation of event rates to allow for optimal risk–benefit assessment and to not scare clinicians away from proper OAC use (either initiation, continued use, or appropriate dosing) due to undue concern over bleeding.…”
Section: Discussionmentioning
confidence: 99%